Cloning and functional validation of early inducible Magnaporthe oryzae responsive CYP76M7 promoter from rice - Vijayan, Joshitha; Devanna, B. N.; Singh, Nagendra K.; Sharma, Tilak R. (Frontiers in Plant Science, 2015)
Cloning and functional characterization of plant pathogen inducible promoters is of great significance for their use in the effective management of plant diseases. The rice gene CYP76M7 was up regulated at 24, 48 and 72 hours post inoculation (hpi) with two isolates of Magnaporthe oryzae Mo-ei-11 and Mo-ni-25. In this study, the promoter of CYP76M7 gene was cloned from rice cultivar HR-12, characterized and functionally validated. The Transcription Start Site of CYP76M7 was mapped at 45 bases upstream of the initiation codon. To functionally validate the promoter, 5′ deletion analysis of the promoter sequences was performed and the deletion fragments fused with the GUS reporter gene were used for generating stable transgenic Arabidopsis plants as well as for transient expression in rice. The spatial and temporal expression pattern of GUS in transgenic Arabidopsis plants and also in transiently expressed rice leaves revealed that the promoter of CYP76M7 gene was induced by M. oryzae. The induction of CYP76M7 promoter was observed at 24 hpi with M. oryzae. We report that, sequences spanning -222 bp to -520 bp, with the cluster of three W-boxes, two ASF1 motifs and a single GT-1 element may contribute to the M. oryzae inducible nature of CYP76M7 promoter. The promoter characterized in this study would be an ideal candidate for the overexpression of defence genes in rice for developing durable blast resistance rice lines.